An Evaluation of the Independence of Ghana's Anti-Corruption Institutions - Donpaala, Stephen Delle; Dauda, Alhassan (Research Parks Publishers, 2023)
Ghana has had a constant progress in cementing its democracy since its restoration to democratic governance in 1992, making it one of the most often cited success stories of democracies in Africa. Despite this achievement, the independence of anti-corruption institutions in Ghana such as the Auditor General,(AG), Commission of Human Rights and Administrative Justice (CHRAJ), Economic and Organised Crime Office (EOCO), Public Procurement Authority, (PPA), Internal Audit Agency (IAA), Office of Special Prosecutor (OSP) and others is over prejudice in terms of appointment of the Heads of these institutions, removal and budgeting as specified in Ghana’s, 1992 Constitution empowering the president of Ghana as the sole appointor, remover and budget allocator hence making it difficult for these institutions to function effectively. This makes it a political gimmick when any other government talk about fighting corruption in its current form of constitutional arrangement. This research uses a qualitative method of collecting data. Due to these constitutional gaps, it shows that corruption remains a scourge that has eaten through the political fabric of the nation. All facets of the Ghanaian government are corrupt and accountability is often lacking. The criminals often get away with it. It is therefore recommended that the appointment, removal and budget of these anti-corruption institutions should be vested on Parliament through the Appointment Committee of Parliament. Their tenure of office should not directly match with any particular elected government tenure.